ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT LITERASI KEUANGAN MAHASISWA (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis UPN “Veteran” Yogyakarta) - Tutik Apriyanti; Sri Astuti; Ichsan Setiyo Budi (Behavioral Accounting Journal, 2021)
This study aims to examine the effect of the variables gender, age, GPA, work experience and parental education level on the level of financial literacy of FEB UPN "Veteran" Yogyakarta students. This study used a purposive sampling method. The determination of the sample in this study used to Slovin formula with an error rate of 10% in order to obtain a research sample of 104 respondents at the Faculty of Economics and Business UPN "Veteran" Yogyakarta. The data collection technique in this research is by using a questionnaire. The analysis used is multiple regression analysis using SPSS (Statistical Package for Social Sciense) version 25. The results of this study indicate that the GPA variable and the level of parental education have a positive and significant effect on the level of student financial literacy while the variables gender, age and work experience do not has a positive and significant affect on the level of student financial literacy.